Eﬀects of Artificial Aging on Seed Vigor and Physiological Characteristics of the Invasive Alien Plant Aegilops tauschii - Ning Wang (Polish Botanical Society, 2021)
The control of invasive plants depends to some extent on the persistence of the soil seed bank. The high temperature (40 °C) accompanied with high humidity (95%) method was used to treat the seeds of the invasive species Aegilops tauschii Coss. The aim of our study was to evaluate the seed vigor and longevity by accelerating aging, to serve as a reference for the evaluation of invasion potential of A. tauschii and corresponding eradication strategy adoption. The results showed that with the extension of aging time, the germination rate (GR), energy (GE), and index (GI) of A. tauschii seeds reduced. All the results were significantly different from the control (CK) since the second day (p 0.05). During the aging process, the seed relative water content (RWC), relative electric conductivity (REC), and thiobarbituric acid (TBARS) level increased, while the superoxide dismutase (SOD) gradually decreased after second day of seed aging. In addition, the aging treatment also caused a continuous decrease in the endogenous gibberellin (GA3) content and a continuous increase in the abscisic acid (ABA) content of the seeds. Thus, a sharp decrease in the GA3/ABA ratio was evident. Finally, the study revealed that the germination inhibitors of A. tauschii were mainly concentrated in the glumes, which was revealed during seed aging. The results of the comprehensive analysis indicated that the changes of the above-mentioned internal factors eventually led to a rapid decline of the seed vigor of A. tauschii. Based on the results of the aging test, and the distribution characteristics of A. tauschii seeds in the soil seed banks, we recommend that soil solarization is one of the effective methods to eradicate the seed bank of A. tauschii.